STUDENTS’ ENGLISH ORAL COMMUNICATION APPREHENSION AT ENGLISH STUDY PROGRAM OF STKIP INSAN MADANI - Widi Syaftinentias; Fajar Wirawan; Loly Novita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Oral communication apprehension is one of the psychological factors. Communication apprehension (CA) is defined as an individual’s level of fear or anxiety associated with their real or anticipated communication with another people. The objective of this research is to know the level of English oral communication apprehension of students at English Study Program at STKIP Insan Madani Airmolek. The research is quantitative research. It was conducted at students of English Study Program of STKIP Insan Madani AirmolekThe instrument used in this research is questionnaire. In this research, the technique analysis date were collecting the data, categorized the data based on indicators, describe the data and make conclusion. The research result showed that the level of English oral communication was in moderate level for 60% of students, 30% students was on high level communication apprehension and 10% was on low oral communication apprehension. Keywords: English speaking skill, Oral communication apprehension, students